The effect of violent conflict on calorie consumption and dietary quality in Iraq - Marta Parigi (Journal of Agricultural Economics, 2023)
By combining 2012 Living Standard Measurement Survey cross-sectional survey responses and georeferenced conflict data, this study quantifies the effect of violent conflict on food security and dietary quality in Iraq. Specifically, it estimates the effect of physical insecurity on different food security dimensions, including caloric consumption and household dietary diversity. Because disrespecting war-related foreign national cemeteries is a war crime that discourages nearby fighting, instrumenting conflict intensity by the exogenous variation in distance between these sites and household place of residence addresses potential sources of bias. The instrumental variable analysis confirms the positive (negative) effect of conflict—deriving from state, non-state and one-sided violence (e.g., attacks by the Islamic State)—on per capita caloric consumption (household dietary diversity), which although counterintuitive is unsurprising given Iraq's relatively high-income levels and changes in dietary pattern. Given that the primary driver of conflict's positive effect on calories is increased consumption of carbohydrates and, to a lesser extent, saturated fat, these results suggest that in countries transitioning to Western-style diets, violent conflict may drive the population toward an unhealthier diet, contributing heavily to a growing national prevalence of nutrition-related non-communicable diseases.
Keywords: 630; conflict; food security; instrumental variables; Iraq